Exploring the impact of intensity and duration of Cu (II) depression on aniline-degrading biosystem: Performance, sludge activity and microbial diversity. (September 2022) - Su, Junhao; Zhang, Qian; Peng, Haojin; Feng, Jiapeng; He, Jing; Zhang, Yunjie; Lin, Bing; Wu, Nanping; Xiang, Yutong
Graphical abstract: Highlights: Aniline-degrading function was slightly impacted under Cu (II) at below 6 mg/L. Pollutant removal performance was disabled quickly under Cu (II) at 10 mg/L. The denitrifying performance was more sensitive to Cu (II) toxicity than nitrifying. High content Cu (II) weakened the Cu (II) absorption and EPS secretion of bioflocs. Abstract: To evaluate the ecological risk of aniline wastewater biodegradation, the aniline wastewater (200 mg/L) was treated in this work under the stress of Cu (II) at 3, 6 and 10 mg/L, respectively. The slight fluctuation of aniline-degrading performance and the significant inhibition of nitrogen removal was caused by the Cu (II) stress at below 6 mg/L. Meanwhile, the tolerance of nitrifying performance to Cu (II) was higher than denitrifying. The collapse of biosystem was caused by the Cu (II) stress at 10 mg/L and the decontamination function was disabled within 8 days. The activity and stability of sludge declined under the increase of Cu (II) content. Microbial diversity results demonstrated that the genera with heavy-metal tolerance represented by Zoogloea and Azospira significantly dominated under the continuously Cu (II) stress. Whereas, the biosystem with these dominant genera did not achieve the comparable aniline and nitrogen removal performance as the control group.